Investigation of the Effects of Land Use on Chemical Water Quality Parameters; A Case Study of Başkonuş-Meydan Dam Lake in Kahramanmaraş - Emre Babur; Ömer Süha Uslu; Cafer Hakan Yılmaz; Muhammet Raşit Sünbül (Aquatic Sciences and Engineering)
Water quality is in constant interaction with and changed according to time and place through natural and anthropogenic factors. It is also known that land use has a significant impact on water quality parameters. In this study, it was aimed to determine the effects of different land-use types (Forest, range and riparian) on water quality and which land-use type supports the most suitable drinking water for watersheds in the Başkonuş Plateau in Kahramanmaraş Province. The field studies were carried out in May 2019, and 2 sampling points were selected from each of the land-use types. Chemical properties (pH, EC) and some element concentrations (19 elements such as Al, As, Cu, B, Zn, Fe, P, Cd, Ca, Co, Cr, Pb, Mg, Mn, Mo, Ni, K, Na, and S) were investigated by using an ICP-OES. According to the results, the water obtained from forest areas is more suitable for drinking, having drinking water quality standards with a high pH value (7.59), and the Sulfur concentration of water obtained from range area (26.72 μg S /L) exceeded and did not comply with drinking water quality standards. When the chemical characteristics of the Meydan Dam were examined according to the regulated water quality standards declared in water pollution laws, it is clear that the dam basin has a high water quality standard (Class I). Therefore, a larger dam that can be built in this basin would be able to supply quality water that the Kahramanmaraş metropolitan municipality needs. Consequently, before deciding on the construction of the dam for drinking water, land-use maps would be created in the basins, and the selection of basins that have dense and qualified forestland would provide quality water.